Facilitators for improvement of psychiatric services and barriers in implementing changes: From the perspective of Finnish patients and family members. (20th November 2020) - Lantta, Tella; Anttila, Minna; Varpula, Jaakko; Välimäki, Maritta
Abstract: The need for psychiatric patients and their family members to have access to quality user‐friendly services has been studied for decades, yet few improvements have been made in treatment services. This study aims to explain how patients and family members have experienced facilitators of improvements, and their thoughts about barriers in the implementation of changes. An explanatory qualitative design was adopted. Data were collected using semi‐structured interviews with eight focus groups made up of a total of 35 participants from mental health associations in Finland. The Theoretical Domains Framework guided the deductive data analysis. The Consolidated Criteria for Reporting Qualitative Studies (COREQ) was followed in the study. Participants in patient and family member associations had similar experiences and thoughts about facilitators of improvements in psychiatric services and barriers in the implementation of changes. For example, both participant groups experienced that promoting more positive roles of professionals could facilitate improvements in psychiatric care. On the other hand, a lack of theoretical competence and interpersonal skills of professionals could hinder change. We conclude that many of the facilitators that patients and families suggested could be addressed by enhancing collaboration and communication, having a more person‐centred approach, focusing on recovery throughout the course of care, and acknowledging staff's well‐being at work. Second, the barriers to implementing changes centre around the limited knowledge and skills of staff, and a paternalistic system that focuses on managing risk and administering treatment.